Cultural Retention and Adaptation among Nepali Immigrants in Canada - Acharya, Sharad (NPRC Journal of Multidisciplinary Research, 2026)
Background: Nepali immigrants in Canada, though a growing community, remain underrepresented in migration and acculturation research. As they navigate life in a multicultural society, they face the dual challenge of preserving cultural heritage while integrating into Canadian social structures.Objective: This study examines how Nepali immigrants in Canada retain cultural traditions while adapting to Canadian society, focusing on identity negotiation, cultural continuity, and intergenerational transmission.Methods: A qualitative approach employing thematic analysis was adopted. Semi-structured interviews were conducted with ten purposively selected participants, including first- and second-generation immigrants and individuals actively involved in community institutions. Data collection continued until thematic saturation was achieved.Results: Major cultural and religious traditions (Dashain, Tihar, Losar, Teej, Buddha Jayanti) remain strongly preserved among first-generation immigrants, while minor rituals show gradual decline among younger generations, reflecting selective cultural retention. Nepali language maintenance faces challenges due to English dominance in schools and peer interactions. Community institutions—including language schools, temples, and cultural organizations—play a vital role in sustaining heritage and fostering ethnic belonging. Digital media contributes significantly to cultural continuity by connecting immigrants to Nepali festivals and practices across borders.Conclusion: Cultural adaptation among Nepali immigrants is a dynamic process wherein first-generation immigrants actively preserve traditions while second-generation youth develop hybrid cultural identities. The study contributes to acculturation theory by demonstrating how integration and retention coexist within multicultural contexts.Novelty: This research addresses a significant gap in diaspora literature by focusing specifically on Nepali immigrants in Canada, examining intergenerational dynamics and the role of community institutions in cultural preservation.